2009
DOI: 10.1590/s0100-204x2009000700013
|View full text |Cite
|
Sign up to set email alerts
|

Estimating water application efficiency for drip irrigation emitter patterns on banana

Abstract: -The objective of this work was to evaluate root and water distribution in irrigated banana (Musa sp.), in order to determine the water application efficiency for different drip irrigation emitter patterns. Three drip emitter patterns were studied: two 4-L h -1 emitters per plant (T1), four 4-L h -1 emitters per plant (T2), and five 4-L h -1 emitters per plant (T3). The emitters were placed in a lateral line. In the treatment T3, the emitters formed a continuous strip. The cultivated area used was planted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
(21 reference statements)
3
9
0
6
Order By: Relevance
“…Calculations using moisture data from one (P 1 ), two (P 2 ), three (P 3 ) and four (P 4 ) monitoring profiles during the experimental period. when water is available in all the profile, the intensity of water extraction is greater near the plant pseudostem (Silva et al, 2009a;Silva et al, 2012;. However, soil sensors are used to monitor moisture with one or two probe sets per plant (Silva et al, 2009b;Souza et al, 2013).…”
Section: Et Variation With Different Numbers Of Radial Distances (R 1mentioning
confidence: 99%
“…Calculations using moisture data from one (P 1 ), two (P 2 ), three (P 3 ) and four (P 4 ) monitoring profiles during the experimental period. when water is available in all the profile, the intensity of water extraction is greater near the plant pseudostem (Silva et al, 2009a;Silva et al, 2012;. However, soil sensors are used to monitor moisture with one or two probe sets per plant (Silva et al, 2009b;Souza et al, 2013).…”
Section: Et Variation With Different Numbers Of Radial Distances (R 1mentioning
confidence: 99%
“…However, root water extraction may vary in space and time regardless of root concentration (Clothier and Green, 1994;Silva et al, 2009;Javaux et al, 2008;Raza et al, 2013). This variability has been studied by Silva et al (2015) for banana crop and the authors reported that it is necessary at least 16 time domain reflectometry (TDR) probes to be installed at a minimum distance from plant of 0.9 m and a minimum soil depth of 0.7 m to prevent an overestimation of banana crop evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used time-domainreflectometry (TDR) to estimate the water flow in unsaturated soils (Wessolek et al, 2008;Silva et al, 2009;Selle et al, 2011;Baram et al, 2012;Séré et al, 2012). In this case, the procedures to use the TDR technique being well-known, the percolation levels can be calculated without the predetermination of the hydraulic properties.…”
Section: Introductionmentioning
confidence: 99%